The Effect of Price, Promotion and Service Quality on Customer Satisfaction at PT. Triguna Karya Nusantara - Agnesda Servina; Ika Baskara (Budapest International Research and Critics University, 2022)
This study aims to determine the effect of Price, Promotion and Service Quality on Customer Satisfaction. Where independent variables consist of Price, Promotion Quality of Service and Customer Satisfaction as its dependent variables, this research was conducted at PT. Triguna Karya Nusantara in the city of Bekasi. The data collection method in this study was a questionnaire filled out by respondents, namely PT. Triguna Karya Nusantara has bought a forklift at least twice. The sampling of 100 respondents in this study used the Purposive Sampling method. The free variable in this study consists of Price, Promotion and Service Quality, while the dependent variable is Customer Satisfaction. The analysis used in this study includes index number analysis, validity test, reliability test, classical assumption test, multiple linear regression analysis and hypothesis testing, which provides for a t-test, F test, and coefficient of Determination (R2). The study's multiple linear regression results show that the price variable has no positive and significant influence on pt. Triguna Karya Nusantara. Second, promotion variables have a positive and significant effect on customer satisfaction of PT. Triguna Karya Nusantara. Third, the variable quality of service has a positive and significant impact on the joy of PT. Triguna Karya Nusantara. The analysis results using the F test can be known price, Promotion and service quality to customer satisfaction.